Gender equity or bust! : on the road to campus leadership with women in higher education - Wenniger, Mary Dee, 1944-; Conroy, Mary Helen (Jossey-Bass higher and adult education series., 2001)
Gender battles still rage on most college and university campuses today. For eight years, Women in Higher Education has reported women's strategic advances in the academy. Its goal is to enlighten, encourage, empower, and enrage women administrators, faculty, and students in higher education. This book is a compendium of lively, hard-hitting articles from the successful newsletter. Its thematic sections blend serious commentary, research results, and practical advice with wry humor.